Financial Incentives and Loan Officer Behavior: Multitasking and Allocation of Effort under an Incomplete Contract. (June 2020) - Behr, Patrick; Drexler, Alejandro; Gropp, Reint; Guettler, Andre
Abstract : We investigate the implications of providing loan officers with a nonlinear compensation structure that rewards loan volume and penalizes poor performance. Using a unique data set provided by a large international commercial bank, we examine the main activities that loan officers perform: loan prospecting, screening, and monitoring. We find that when loan officers are at risk of losing their bonuses, they increase prospecting and monitoring. We further show that loan officers adjust their behavior more toward the end of the month when bonus payments are approaching. These effects are more pronounced for loan officers with longer tenures at the bank.